Financial Performance As Mediator Between Size, Liquidity, And Ownership On Firm Value - B. Andini Nugrahaning Widhi; Herry Subagyo; Retno Indah Hernawati; Vincent Didiek Wiet Aryanto; Dwi Eko Waluyo (Politeknik Ganesha Medan, 2025)
The world economy has been in turmoil for the past five years, causing an impact on the company's economy due to the Covid-19 pandemic. where this study is to explore how financial performance mediates the impact of company size, liquidity, and foreign ownership on company value in the consumer goods industry listed on the Indonesia Stock Exchange during 2018 to 2022. Regression analysis, along with the Sobel test, is used to test this relationship. Interestingly, despite the expectation that financial performance can bridge the gap between the independent and dependent variables, the results of the Sobel test show no mediation effect. As a result, the relationship between company size, liquidity, foreign ownership, and company value is direct. For further research, expanding the scope of the study to cover various sectors, extending the time period, and combining various financial ratios can provide a more comprehensive understanding.